Perancangan Aplikasi Makanan Tempe Sebagai Kearifan Lokal (Local Wisdom) dan Diplomasi Kuliner - Yanty Faradillah; Susi Ekalestari (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
Tempe as a national food and local wisdom is expected to become more popular in the world. To realize this, more vigorous promotion is needed. Tempe is one of the functional foods that has antioxidant, antimicrobial, anticancer, antihypertensive, antithrombotic and hypocholesterolemic properties. The most effective and subtle way of popularizing something to the global market is through socio-economic diplomacy. One of them, is through culinary diplomacy. In addition, a synergy between local wisdom and information technology is needed that is beneficial for the progress of the nation. So, it is necessary to make an application in English to introduce tempeh food for international information. The outputs of this application are: 1) History of Tempe; 2) Video of the tempe industry in Indonesia; 3) How to make processed tempeh (contains text and video); 4) Video recipes for various types of tempeh; 5) Video sharing of processed tempeh recipes from application members; 6) Visitors can buy tempeh from Micro, Small and Medium Enterprises (SMEs); and 7) Links to Websites of Indonesian Embassies (KBRI) around the world. The curious effect that this application wants to build is to make visitorscome to Indonesia so as to increase the world of tourism by making tempeh as culinary diplomacy such as: 1) more foreign investment goes to Indonesia; 2) a larger market abroad is open for Indonesian commodity products; and 3) more foreign tourists come to Indonesia.